A Critical Analysis of Minutes of Companies Proceeding in Nigeria: Problems and Recommendations - Okonkwo, Ifeanyi Emmanuel (International Journal For Research In Business, Management And Accounting, 2015)
Over the years, we have seen and heard of corrupt Directors forging the minutes and resolutions of a company in other to fraudulently obtain loans from banks. We have heard and seen forceful takeovers without proper resolutions only for us to find such lies enshrined in a ghost-minutes of the company. We have seen present members rendered absent in the minutes even though we can swear we saw them present. Yes! virtually all that a company does is recorded and in the event of a dispute, enquiry, query, investigation, meetings, resolutions, et al, one important document or record which substantially stand as evidence in resolving or denying any transaction is the minutes of the proceedings of the company. Indeed any foreign holding or subsidiary or partnership company as well as investors may want to know about the legal effects of the Minutes. The minutes become in the letters of the Companies & Allied Matters Act, a prima facie evidence of companies proceedings. The effect is that whatever is so recorded in the minutes, so far the chairman’s signature is affixed, is the truth of the proceedings. Although, the Act allowed for a rebuttal of the minutes with other proofs, but the Act did not state any other way in which the content of the minutes may be disproved. Again the form in which minutes are to be kept in line with the present 1990 Act is another setback. Indeed, prior to the enactment of CAMA and with recent judicial authorities, the judicial view was that Minute entries made in loose sheets of paper, whether kept in a file or fastened together in a bound book subsequently, were not admissible/permitted evidence of the Minutes of the deliberations and decisions taken at such a meeting (See Onwuka v. Taymani & Ors [1965] NCLR page 203; and the English case - Heart of Oaks Ass. v. James Lower & Sons Ltd[1936] Ch.D page 26) Later the Supreme Court in Chika Brothers Case held differently in interpreting the 1968 Act which unfortunately does not tally literarily with the present 1990 Act. Infact, the situation becomes more disturbing going by the general rule of evidence that no extrinsic evidence of certain documentary evidence is allowed. We can indeed only hope to come under its exceptions, but again, practically speaking, its exceptions are difficult to prove within the settings of a company. This leads to grave dangers in that anyone in the company, especially its Directors, may forge a resolution or otherwise against the company provided the chairman’s signature can be forged or generated (moreso, if it is the chairman). The same goes for the board meetings and others. The very principle of corporate governance and its checks and balances is surely incomplete without a proper legal framework to safeguard that most indispensable and invaluable book of a company – The minutes.